Improved coomassie blue dye-based fast staining protocol for proteins separated by SDS-PAGE - Májek, Pavel; Riedelová-Reicheltová, Zuzana; Pecánková, Klára; Dyr, Jan E (PloS one, 2013)
The time required to visualize proteins using Coomassie Blue dye has been significantly reduced with the introduction of fast staining protocols based on staining with a Coomassie Blue dye solution at boiling temperatures. However, fast stainings suffer from high gel backgrounds, reducing the signal-to-noise ratio and limiting the number of detectable spots in the case of 2D SDS-PAGE. The aim of this work was to eliminate the high gel background, and thus improve fast staining protocols based on Coomassie Blue dye. We show that merely replacing water with a 4 mM EDTA washing solution at boiling temperatures, results in a transparent gel background within 50 to 60 minutes of destaining. Moreover, when a combination of imidazole-zinc reverse staining and Coomassie Blue-based fast staining is used the sensitivity is improved significantly; nanogram amounts of proteins can be detected using 1D SDS-PAGE, and about 30% to 60% more spots can be detected with 2D SDS-PAGE in plasma, platelet, and rat brain tissue samples. This work represents an optimized fast staining protocol with improved sensitivity, requiring between 60 to 75 minutes to complete protein visualization.
Keywords: indikátory a reagencie; Electrophoresis, Polyacrylamide Gel; Rosaniline Dyes; proteiny; rosanilinová barviva; elektroforéza v polyakrylamidovém gelu; Indicators and Reagents; Proteins